An investigation of SMART Recovery: protocol for a longitudinal cohort study of individuals making a new recovery attempt from alcohol use disorder. Issue 2 (3rd February 2023) - Kelly, John F; Levy, Samuel A; Hoeppner, Bettina B
Abstract : Introduction: Alcohol use disorder (AUD) remains one of the most pervasive of all psychiatric illnesses conferring a massive health and economic burden. In addition to professional treatments to address AUD, mutual-help organisations such as Alcoholics Anonymous (AA) and newer entities like Self-Management and Recovery Training (SMART Recovery) play increasingly important roles in many societies. While much is known about the positive effects of AA, very little is known about SMART. Hence, this study seeks to estimate real-world patterns of utilisation and benefit from SMART Recovery as well as explore for whom (moderators) and how (mechanisms) SMART confers recovery benefits. Methods and analysis: Naturalistic, longitudinal, cohort study (n=368) of individuals with AUD recruited between February 2019 and February 2022, initiating a new recovery attempt who self-select into one of four groups at study entry: (1) SMART Recovery; (2) AA; (3) SMART+AA; (4) Neither SMART nor AA; (stratified by Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM 5) severity markers), with assessments conducted at intake, and 3 months, 6 months, 9 months, 12 months, 18 months and 24 months. Primary outcomes are: frequency of SMART and AA meetings attendance; per cent days abstinent and per cent days heavy drinking. Secondary outcomes include psychiatric distress; quality of life and functioning. Moderator variables include sex/gender; race/ethnicity; spirituality. Mediational variables include social networks; coping skills; self-efficacy; impulsivity. Multivariable regression with propensity score matching will test for patterns of attendance and effects of participation over time on outcomes and test for mechanisms and moderators. Ethics and dissemination: This study involves human participants and was approved by the Massachusetts General Hospital Institutional Review Board (Protocol #: 2017P002029/PHS). Results will be published in peer-reviewed journals and presented at conferences. Registration: This is a non-randomised, naturalistic, longitudinal, cohort study, and thus was not registered in advance. Results, therefore, should be considered exploratory.